Hyperoside as a UV Photoprotective or Photostimulating Compound-Evaluation of the Effect of UV Radiation with Selected UV-Absorbing Organic Compounds on Skin Cells - Moukova, Anna; Malina, Lukas; Kolarova, Hana; Bajgar, Robert (International journal of molecular sciences, 2023)
Ultraviolet (UV) radiation is a non-ionizing radiation, which has a cytotoxic potential, and it is therefore necessary to protect against it. Human skin is exposed to the longer-wavelength components of UV radiation (UVA and UVB) from the sun. In the present paper, we focused on the study of eight organic UV-absorbing compounds: astragalin, beta-carotene, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, hyperoside, 3-(4-methylbenzylidene)camphor, pachypodol, and trans-urocanic acid, as possible protectives of skin cells against UVA and UVB radiation. Their protective effects on skin cell viability, ROS production, mitochondrial membrane potential, liposomal permeability, and DNA integrity were investigated. Only some of the compounds studied, such as trans-urocanic acid and hyperoside, had a significant effect on the examined hallmarks of UV-induced cell damage. This was also confirmed by an atomic force microscopy study of morphological changes in HaCaT cells or a study conducted on a 3D skin model. In conclusion, hyperoside was found to be a very effective UV-protective compound, especially against UVA radiation. Commonly used sunscreen compounds such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 3-(4-methylbenzylidene)camphor turned out to be only physical UV filters, and pachypodol with a relatively high absorption in the UVA region was shown to be more phototoxic than photoprotective.
Keywords: Humans; pachypodol; kyselina urokanová; trans-urocanic acid; kůže; UV-absorbing compounds; lidé; ultrafialové záření; astragalin; přípravky chránící proti slunci; Sunscreening Agents; 2-hydroxy-4-methoxybenzophenone; hyperoside; phototoxicity; 3-(4-methylbenzylidene)camphor; Ultraviolet Rays; Urocanic Acid; 2,4-dihydroxybenzophenone; beta-carotene; Skin